Perineal Massage Improves the Dyspareunia Caused by Tenderness of the Pelvic Floor Muscles - Ana Paula Moreira da Silva; Mary Lourdes Montenegro; Maria Beatriz Ferreira Gurian; Andreia Moreira de Souza Mitidieri; Lucia Alves da Silva Lara; Omero Benedicto Poli Neto; Julio Cesar Rosa e Silva (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
ABSTRACT Aim: To evaluate the long-term effectiveness of perineal Thiele massage in the treatment of women with dyspareunia caused by tenderness of the pelvic floor muscles. Methods: A total of 18 women with diagnoses of dyspareunia caused by tenderness of the pelvic floor muscles were included in the study. The women were divided in two groups: the dyspareunia (D) group - 8 women with dyspareunia caused by tenderness of the pelvic floor muscles; and the chronic pelvic pain group (CPP) group - 10 women with dyspareunia caused by tenderness of the pelvic floor muscles associated with CPP. Each patient filled out the Visual Analogue Scale (VAS), the McGill Pain Index, the Female Sexual Function Index (FSFI) and the Hospital Anxiety and Depression Scale (HADS). After an evaluation, the women underwent transvaginal massage using the Thiele technique over a period of 5 minutes, once a week for 4 weeks. Results: All women had significant improvements in their dyspareunia according the VAS and the McGill Pain Index (p < 0,001), but the HADS scores did not show significant differences. Regarding sexual function, the D group showed improvements on all aspects of sexual function, while the CPP group showed differences only in the pain domain. Conclusion: Thiele massage is effective in the treatment of dyspareunia caused by tenderness of the pelvic floor muscles with a long-term pain relief.